Relation between degree of obesity and site-specific adipose tissue fatty acid composition in a Mediterranean population - Garaulet, Marta; Hernandez-Morante, Juan Jose; Tebar, Francisco Javier; Zamora, Salvador (Nutrition (Burbank, Los Angeles County, Calif.), 2011)
Obesity itself could be a key factor determining fatty acid (FA) composition of adipose tissue (AT). A Mediterranean diet influences this relationship. However, a relation between different overweight and obesity levels (including morbidly obese subjects) and AT FA pattern has not been fully established. The objective of the present study was to analyze potential differences in AT FA composition attending to degree of obesity in patients who follow a Mediterranean dietary pattern. Our study comprises 60 patients classified as overweight, obese, or morbidly obese (20 subjects in each group). Dietary composition was assessed by a 7-d record, and visceral and subcutaneous AT FAs were analyzed by gas chromatography. Cardiometabolic risk-related parameters were also assessed. Our results showed that dietary habits were similar among groups, although palmitic intake was higher and palmitoleic intake was lower in the morbidly obese group. Concerning AT, we observed significant differences in the visceral depot. Concretely, both total monounsaturated FA ( P = 0.039) and palmitoleic acid ( P = 0.008) were higher in overweight subjects. Most differences were found in the subcutaneous tissue. Among them, n-9 and total monounsaturated FA ( P < 0.001) were significantly higher again in overweight subjects, while 22:6 n-3 was higher in morbidly obese subjects. Subcutaneous adipose dihommo-γ-linolenic content and dietary palmitic and palmitoleic acids were independent predictors of body mass index. We confirm the relationship between degree of obesity and dietary and AT FA composition in this Mediterranean population. Despite a similar dietary pattern among groups, overweight and morbidly obese patients have a less detrimental FA profile than obese patients, probably due to differences in adipose tissue metabolism.